2022
DOI: 10.21037/apm-21-2139
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and intraoperative tubal sterilization are risk factors for high incidence of pain after cesarean delivery: a prospective observational study

Abstract: Background: Postcesarean delivery pain leads to several adverse maternal outcomes. The primary objective of this study was to determine the incidence of moderate-to-severe pain after the use of spinal morphine for cesarean delivery. The secondary aim was to identify factors influencing moderate-to-severe pain.Methods: This was a prospective observational study. The inclusion criteria were a patient age of ≥18 years, and undergoing elective cesarean delivery under spinal anesthesia with intrathecal morphine (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…GDM is a common complication of pregnancy, and the incidence of GDM rapidly increased in recent years ( 1 ). Pregnant women with GDM tend to deliver by cesarean section, and despite the short duration of hyperglycemia in GDM patients, it is still a risk factor for postcesarean pain ( 2 ), some studies have found that postcesarean pain is more severe in women with GDM than in those without GDM, and postoperative pain requires more sufentanil to achieve satisfactory analgesia after surgery ( 3 , 4 ). Clinicians should focus on postoperative analgesic management in patients with GDM to improve the effectiveness of postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDM is a common complication of pregnancy, and the incidence of GDM rapidly increased in recent years ( 1 ). Pregnant women with GDM tend to deliver by cesarean section, and despite the short duration of hyperglycemia in GDM patients, it is still a risk factor for postcesarean pain ( 2 ), some studies have found that postcesarean pain is more severe in women with GDM than in those without GDM, and postoperative pain requires more sufentanil to achieve satisfactory analgesia after surgery ( 3 , 4 ). Clinicians should focus on postoperative analgesic management in patients with GDM to improve the effectiveness of postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusion: Compared to sufentanil PCA, adding low dose of esketamine significantly reduced the consumption of sufentanil while providing equally effective post cesarean analgesia in the patients with gestational diabetes. KEYWORDS gestational diabetes, cesarean delivery, intravenous patient-controlled analgesia, esketamine, prospective study 1 Background GDM is a common complication of pregnancy, and the incidence of GDM rapidly increased in recent years (1). Pregnant women with GDM tend to deliver by cesarean section, and despite the short duration of hyperglycemia in GDM patients, it is still a risk factor for postcesarean pain (2), some studies have found that postcesarean pain is more severe in women with GDM than in those without GDM, and postoperative pain requires more sufentanil to achieve satisfactory analgesia after surgery (3,4).…”
mentioning
confidence: 99%